Multidimensional Poverty Index of Niger State, Nigeria - Rossazana, Ab-Rahim; Musa, Mohammed (Human Resource Management Academic Research Society (HRMARS), 2019)
PPast studies have tended to focus on measuring monetary poverty based on poverty line income; thus, this study aims to investigate the monetary poverty and the multidimensional poverty index (MPI) of 432 households in Niger State, Nigeria. Interestingly, the results indicate 13 per cent of those above poverty line income (non-poor) are found to be multidimensional poor. Hence, this paper suggests that the monetary measure of poverty should be complemented with multidimensional measure. The results of this study also show poverty is apparent in essential living standard and health among the households as spelled out by inadequate access to portable drinking water, poor sanitary facilities, electricity supply, primitive cooking fuel as well as limited access to improved health facilities. The results imply that effective policies towards general infrastructural development will greatly contribute to poverty reduction.